Autumn's kiss : an Autumn falls novel - Thorne, Bella, 1997-; Allen, Elise (Thorne, Bella, 1997- Autumn Falls novel., 2015)
The wish-granting diary Autumn Falls' father left her stops working and high school junior Autumn must figure out her love life on her own until she is given a map that will take her wherever she wants to go, but rather than being a fun opportunity, it leads to life-changing consequences.